Scripting the mobile development subject: a case study of shipping second-hand bicycles to Africa - Baker, Lucy (Social & cultural geography, 2021)
This study critically examines how development interventions are imagined for singular places and subjects through a political process of product scripting that reconfigures the socio-technical meaning of second-hand objects from unwanted commodities to solutions that are appropriate for sub-Saharan Africa. Tracing the flow of second-hand goods demonstrates how development subjects are imagined to be adult, economically productive, rural beings. The paper finds that the second-hand mountain bicycle is inserted into an imagined place with a predetermined purpose that does not attend to alternative and heterogeneous urban and rural identities and needs. The paper highlights the compromises undertaken in designing development interventions as they are entangled with processes of waste recycling, commodification and philanthropy.